The Influence of Interest Organisations on Swedish Rental Housing – Implications for Corporatist Theory - Bo Bengtsson; Martin Grander (Critical Housing Analysis)
Although academic definitions of ‘corporatism’ differ, the concept is generally about organisational influence on state politics. Around 1980, Sweden was regarded as the archetype of welfare-state corporatism, but around the turn of the millennium the broad representation of organised interests in state politics was largely abolished. However, in the housing sector, strong interest organisations have continued to play a dominant and institutionalised role. Rents are negotiated collectively between organisations of estate owners and tenants, and these organisations also have strong influence on rental legislation and on housing policy more generally. We argue that this system should be seen as corporatist and to that end suggest a somewhat modified version of Philippe Schmitter’s well-established definition of corporatism. We claim that our ‘view from housing’ may contribute to the increased relevance of corporatism theory also in studies of other welfare sectors where market distribution is increasingly important.